Pengaruh Karakter Eksekutif, Struktur Modal dan Pertumbuhan Penjualan terhadap Tindakan Penghindaran Pajak - Tika Bella Agustini; Eka Kusuma Dewi (Fakultas Ekonomi Universitas 45 Surabaya, 2026)
This study aims to examine the influence of executive character, capital structure, and sales growth on tax avoidance in primary consumer goods companies, particularly the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during 2019–2024. The research applies a quantitative approach using descriptive analysis and multiple linear regression, with data processed through EViews 13. The sample was determined through purposive sampling, resulting in 22 companies and 132 firm-year observations. Financial data were collected from audited annual reports available on the IDX official website and each company’s website. The findings indicate that executive character, capital structure, and sales growth simultaneously have a significant impact on tax avoidance. Partially, executive character shows a significant negative effect, suggesting that executives with strong ethical values are less likely to engage in aggressive tax avoidance strategies. In contrast, capital structure and sales growth do not significantly influence tax avoidance practices. Overall, the study emphasizes the role of ethical leadership and corporate governance in enhancing tax compliance. It also provides practical implications for policymakers and stakeholders in promoting responsible tax behavior and sustainable corporate practices in emerging markets